2022
DOI: 10.3389/fphar.2022.857015
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol From Penthorum chinense Pursh Attenuates Hepatic Ischemia/Reperfusion Injury by Suppressing Oxidative Stress and Inflammation Through Activation of the Nrf2/HO-1 Signaling Pathway

Abstract: The purpose of this study is to investigate the protective effect of kaempferol (KAE), the main active monomer from Penthorum chinense Pursh, on hepatic ischemia/reperfusion injury (HI/RI) and its specific mechanism. HI/RI is a common complication closely related to the prognosis of liver surgery, and effective prevention and treatment methods are still unavailable. Ischemia/reperfusion (I/R) injury is caused by tissue damage during ischemia and sustained oxidative stress and inflammation during reperfusion. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Recent research showed that quercetin reduced liver inflammation and fibrosis by modulating M1 macrophage polarization [ 39 ]. Kaempferol was found to mitigate oxidative stress and inflammation by suppressing the NF-κB/p65 and Nrf2/HO-1 pathways [ 40 ]. It treats CH by attenuating HBsAg and HBeAg, activating caspase-3, and down-regulating the PI3K-Akt signaling pathway [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research showed that quercetin reduced liver inflammation and fibrosis by modulating M1 macrophage polarization [ 39 ]. Kaempferol was found to mitigate oxidative stress and inflammation by suppressing the NF-κB/p65 and Nrf2/HO-1 pathways [ 40 ]. It treats CH by attenuating HBsAg and HBeAg, activating caspase-3, and down-regulating the PI3K-Akt signaling pathway [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is a key transcription factor for cell regulation of OS, which can activate the transcription and expression of downstream anti-OS-related enzymes, such as HO-1 and SOD to eliminate the abnormal accumulation of ROS in cells, thereby alleviating OS injury [ 77 , 78 ]. ROS is crucial in the stimulation of NLRP3 inflammasome, and suppression of ROS levels in cells can inhibit the stimulation of NLRP3 inflammasome [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, quercetin and kaempferol protected testicular SCs from oxidative stress injury and improved their resistance to heat stress, which was consistent with previous studies [ 61 , 62 ]. Quercetin and kaempferol have a weak ability to improve SOD activity of heat-damaged supporting cells, but for flavonoid monomers, their antioxidant ability lies not only in improving the level of antioxidants, such as SOD but also in their unique active structure to prevent and eliminate oxygen free radicals [ 63 , 64 ]. Quercetin has one more ortho phenolic hydroxyl than kaempferol.…”
Section: Discussionmentioning
confidence: 99%